(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
he present paper seeks to analyse a project of creating and running a system of lodgings which were created to accommodate the so-called “children of Morelia”. he ordeal of the 464 Spanish children who arrived in Mexico in 1937 was marked by a strong polemic and political ights from the moment of their arrival. As they were the object of propaganda between opposing political groups, their integration in Mexico was made diicult and it also afected negatively the development of the centre which hosted them. Around 1943, the situation in the Spanish-Mexican school of Morelia was no longer sustainable and the authorities decided to close it down. As most youngsters quit school or were just about to inish their primary school studies, some help had to be ofered to them so that they could continue their studies or look for a job without being let alone or cut of from their peers. It is in this context that the “casas-hogar” (‘houses-home’) Federación de Organismos de Ayuda a los Republicanos Españoles (FOARE) Project started, which worked relatively successfully for ive years. he article analyses the economic and institutional development of these lodgings, as well as the life conditions of its inhabitants.